1989
DOI: 10.1007/bf00320268
|View full text |Cite
|
Sign up to set email alerts
|

High-dose IgG treatment for neonatal alloimmune thrombocytopenia

Abstract: Twelve children with neonatal alloimmune thrombocytopenia (NAT) due to Zwa incompatibility were treated with intravenous IgG (IVIG). Total doses ranged between 1 and 9 g. Ten out of 12 infants had a favorable response. It is concluded that IVIG can serve as an emergency treatment in NAT if material (or compatible) platelets are not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 12 publications
1
28
1
1
Order By: Relevance
“…Alloantibodies against platelet-specific alloantigens, in particular HPA-1a, can cause severe thrombocytopenia, which may require treatment with high-dose intravenous immune globulin and plasma exchange. 8,9 Neither of the kidney-transplant recipients we studied had a response to these therapies. Patient 2 died of multiorgan failure and bowel perforation related to a he- t r a n s p l a n t a t i o n P a t i e n t 1 a f t e r t r a n s p l a n t a t i o n O r g a n matoma in the bowel wall.…”
Section: Discussionmentioning
confidence: 99%
“…Alloantibodies against platelet-specific alloantigens, in particular HPA-1a, can cause severe thrombocytopenia, which may require treatment with high-dose intravenous immune globulin and plasma exchange. 8,9 Neither of the kidney-transplant recipients we studied had a response to these therapies. Patient 2 died of multiorgan failure and bowel perforation related to a he- t r a n s p l a n t a t i o n P a t i e n t 1 a f t e r t r a n s p l a n t a t i o n O r g a n matoma in the bowel wall.…”
Section: Discussionmentioning
confidence: 99%
“…Small and non-randomised studies have shown that the infusion of IVIG may produce a rise in platelet count in 75% of cases 8. A dosage of 1 g/kg body weight for 2 days or 400 mg/kg for 5 days instead of 3×0.8 g/kg in 1 week might have been more efficient.…”
Section: Discussionmentioning
confidence: 99%
“…The usual recommended dose of IVIG is 2 g per kg administered either as 0.4 g per kg daily for 5 days or as 1 g per kg on 2consecutive days, the latter regimen being preferentially selected in our survey 8 . High‐dose IVIG has been repeatedly reported to be effective in cases of NAIT; however, the evidence derives from small case reports without a control group 24‐26 …”
Section: Discussionmentioning
confidence: 99%